2019
DOI: 10.1039/c8gc03750g
|View full text |Cite
|
Sign up to set email alerts
|

Anisole: a further step to sustainable hydroformylation

Abstract: Anisole, a solvent with an impressive sustainability rank, is an excellent alternative for hydroformylation, an industrially important homogeneously catalyzed reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 47 publications
2
30
0
Order By: Relevance
“…entries 2 and 6). Anisole has a much better sustainability rank than toluene and even than p-cymene, [33] and we have recently found it was an excellent solvent for hydroformylation [34]. Although the selectivity for aldehyde 5a in the reaction in anisole was slightly lower than in toluene, it was still reasonably high (85% vs. 91%, cf.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 92%
See 1 more Smart Citation
“…entries 2 and 6). Anisole has a much better sustainability rank than toluene and even than p-cymene, [33] and we have recently found it was an excellent solvent for hydroformylation [34]. Although the selectivity for aldehyde 5a in the reaction in anisole was slightly lower than in toluene, it was still reasonably high (85% vs. 91%, cf.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 92%
“…In a further study, we decided to test other solvents, with higher sustainability rankings than toluene, as a reaction medium for the hydroformylation of 3a. p-Cymene has been successfully employed by us in hydroformylation [34] and metathesis. [35] For the system with p-cymene, the catalytic results were similar to those obtained in toluene ( Table 3, cf.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Column chromatography was performed on silica gel to afford the product 2-phenylacrylaldehyde [9] (4) (24.3 mg, 74% yield) as a colorless oil. 1 (1,1-diethoxypropan-2-yl)benzene [10]…”
Section: Synthesis Of 3u Via Pd-catalyzed Suzuki Alkylations Of Vinylmentioning
confidence: 99%
“…In 2012, the Zhou group reported that α-aryl vinyl acetals could be nicely prepared via selective α arylation of acrolein diethyl acetal under Heck conditions with Pd[(dba)2]/dppf as the catalyst, but a dramatic effect of steric hindrance was observed (eq 5). 10 Although α-substituted alkenyl acetals could be synthesized according to those methods mentioned above, a modular and general protocol is still highly desirable. Inspired by our recent work on the introducing aryl group at α position of various Michael acceptors based on C−C cross-coupling reactions, 11 I envision that straightforward synthesis of α-substituted alkenyl acetals would be feasible via Pd-catalyzed Suzuki arylation and alkylation of vinylhalide (eq 6).…”
mentioning
confidence: 99%
“…The combination of these factors has seen chemists seek alternative solvent systems to address these concerns. Examples of such alternative, more environmentally friendly solvents include dihydrolevoglucosenone (Cyrene TM ) [ 2 ], RodiaSolv© PolarClean [ 3 , 4 ] and bio-derived lignin pyrolysis oil methyl ether [ 5 ], in particular various substituted anisoles [ 6 ].…”
Section: Introductionmentioning
confidence: 99%